THE EXISTENCE OF JAVANESE ETHNIC IN THE TOWN OF JANTHO - Munadia Yunady Azmi; Ikhwan (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
This paper is entitled The Existence of Javanese Ethnic in the Town of Jantho. This scientific study focuses on the history of the existence of Javanese ethnic during the transmigration program to the Town of Jantho Aceh Besar. The purpose of this paper is to examine further the identification of the number of Javanese Ethnic, fields of livelihood, ethnic interaction with local communities, and factors supporting and inhibiting the existence of Javanese Ethnic. The research used a qualitative approach with observation, interview, and documentation. The data were analyzed through a descriptive qualitative approach. The results showed that the transmigration process in Aceh began during the New Order era. The presence of Javanese ethnics to Jantho through various stages under the direction of government programs starting through providing various kinds of infrastructures. The type of economy they develop is agriculture/plantation, household economy, traders, and others. This is advantageous for them compared to their narrow area of ​​employment in Java. Javanese ethnic maintains harmony among each other well. The supporting factors consist of infrastructure, mixed marriage, culture, and social, while the inhibiting factor is conflict.